ANALISIS MEKANISME PELAYANAN PADA BADAN PENGELOLAAN KEUANGAN DAN PENDAPATAN DAERAH (BPKPD) KABUPATEN WAJO - Burhanuddin Burhanuddin; Najeminur Najeminur (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
This study aims to find out how good the Public Service Mechanism is at the Regional Revenue and Financial Management Board of Wajo Regency. The type of research used is a type of survey with a quantitative associative approach, while the data collection techniques used are observation, questionnaire and documentation. The population and sample in this study are some of the employees at the Regional Revenue and Financial Management Agency of Wajo Regency. Sampling in this study was using the Taroyamane Formula because the population was relatively large so that the sample in this study was 43 people. The results of this study indicate that the public service mechanism at the Wajo Regency Regional Revenue and Financial Management Agency is in very good criteria.